DEKONSTRUKSI PEMAHAMAN PENYELESAIAN SENGKETA BISNIS (EKONOMI DAN KEUANGAN) BERASPEK PIDANAMELALUI PROSEDUR PERDAMAIAN. Menuju Proses Peradilan Pidana Rekonsiliatif - IBNU ARTADI (Fakultas Hukum Universitas Swadaya Gunung Jati, 2011)
DECONSTRUCTION OFDISPUTESETTLEMENTUNDERSTANDINGBUSINESS(ECONOMIC ANDFINANCIAL), WHICH CONTAINSASPECTS OFCRIMINALTHROUGHPROCEDURE OF PEACE. Towardthe Reconciliatory criminal justiceprocessDispute settlementbusiness(economicand financial) containingaspects ofcriminal out of the justice, through theproceduresof peace, is not interpretedas a compromiseby eliminatinglegal process, but it remainsa majorfocusattentionon theestablishment ofharmonyamong theoffender, victimandcommunity.